PERLINDUNGAN HUKUM HAK CIPTA TEHADAP PPEMILIK LAGU ATAS PERBUATAN PENGUNDUHAN LAGU MELALUI SITUS TANPA BAYAR DI INTERNET - Teresia, Rita; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The song is included in the creation of objects protected by the Copyright Act as mentioned in Article 40 paragraph (1) letter d. The act of downloading songsthrough the site without paying or illegal adverse economic rights of copyright owners and contrary to Law Number 28 Year 2014 About Copyright.Problems in this thesis includes two (2) things are, how law enforcement action against downloading of songs through the site without paying on the internetbased on Copyright Act in District Sail, Pekanbaru. and how efforts to be made by the Regional Office of the Ministry of Justice and Human Rights Riau to overcome.The general objective of this study was to fulfill the terms andthesis in order to obtain a law degree at the Faculty of Law, University of Riau, broaden knowledge, especially in the field of civil law.This research is using this type of sociological research, meaning research by examining the legal aspects to see the legislation in forceand compared with that obtained in the execution of the field by way of a survey.Analysis of materials research in this thesis using qualitative methods, in order to draw conclusions using deductive method.This study shows that the enforcement of copyright laws in the District of Sail, Pekanbaru still not running properly marked still many actors downloading of songsThe District of Sail despite socialization. Efforts made by the Regional Office of the Ministry of Justice and Human Rights Riauis to conduct socialization to urge respect and prohibit copyright infringement and conduct investigations related to the reports submittedwhich is handled by the Civil Servants (investigators) and aided by police investigators conducted in accordance with the Copyright Act.Society should appreciate the creative works of others and does not violate the existing rules,Law enforcement officers must carry out their duties and obligations properly in order to reduce the particular song copyright infringement on the Internet.Keywords: Copyright Protection, Download Songs, World Without Pay.